Thucydides in Gaul: The Siege of Plataea as Caesar’s Model for his Siege of Avaricum - Krebs, Christopher B. (Histos, 2016)
In his account of the Roman siege of Avaricum (BG 7.14–28), Caesar adapts and alludes to Thucydides’ description of the siege of Plataea (2.75–7). This is evinced by instances of translation and close paraphrases and numerous common narrative details; and with the help of the verbs imitari and tradere, Caesar even seems to signpost his engagement with Thucydides. He thus enhances both his own narrative and his accomplishment in Gaul.